Lipid peroxidation and generation of hydrogen peroxide in frozen-thawed ram semen cryopreserved in extenders with antioxidants - Maia, Marciane da Silva; Bicudo, Sony Dimas [UNESP]; Sicherle, Carmen Cecilia [UNESP]; Rodello, Leandro [UNESP]; Saltaren Gallego, Isabel Cristina [UNESP] (Elsevier B.V., 2010)
The objective of this study was to evaluate the effect of addition of the antioxidants Trolox and catalase to a ram semen cryopreservation extender on lipid peroxidation and hydrogen peroxide generation on the extender and in the thawed semen. Semen was collected from 23 Santa Ines rams (one ejaculate per ram) and diluted at 32 degrees C to a concentration of 400 x 10(6) cells/ml in one of the following solution: Iris-egg yolk extender (control), or the same extender supplemented with either 50 mu M Trolox/10(8) sperm (Trolox), 50 mu g catalase/ml (Catalase) or a combination of Trolox and catalase (Tro + cat, 50 mu M Trolox/10(8) sperm and 50 mu g catalase/ml). The semen was loaded into 0.25 ml straws, cooled and frozen in a programmable freezer and subsequently stored in liquid nitrogen. Prior to evaluation, frozen straws were thawed in a water bath (42 degrees C for 20 s). Lipid peroxidation (LPO), both spontaneous and catalyzed, on the semen and the extender were measured using the thiobarbituric acid (TBA) assay in accordance with the method described by Buege and Aust (1978). Hydrogen peroxide (H(2)O(2)) generation was measured using the horseradish peroxidase-dependent oxidation of phenol red to a derivative with absorbance at 610 nm, according to the method described by Pick and Keisari (1980). Spontaneous LPO resulted in the least production of thiobarbituric acid-reactive substances (TBARS) in the Tro + cat (1.37 +/- 0.02 nMol/10(8) sperm), compared to amounts in the other treatments groups. In the catalyzed LPO experiments, the least (P < 0.05) amounts of TBARS were observed in Trolox (2.52 +/- 0.02 nMol/10(8) sperm) and Tro + cat (2.54 +/- 0.02 nMol/10(8) sperm) groups, compared to the control (3.81 +/- 0.02 nMol/10(8) sperm) and catalase (3.83 +/- 0.02 nMol/10(8) sperm) groups. Hydrogen peroxide generation was less (P < 0.05) in the Trolox (6.00 +/- 0.18 nMol/40 x 10(6) sperm/+/- 40 min) and Tro + cat (6.08 +/- 0.18 nMol/40 x 10(6) sperm/+/- 40 min) groups than in the control (6.97 +/- 0.18 nMol/40 x 10(6) sperm/+/- 40 min) and catalase (6.53 +/- 0.18 nMol/40 x 10(6) sperm/+/- 40 min) groups. Compared to the control group, Trolox and catalase treatment significantly reduced TBARS in catalyzed LPO and hydrogen peroxide concentrations in the samples (P < 0.05). ROS (reactive oxygen species) generation occurred in all extenders, without sperm cells. The data presented provide evidence that ROS are produced in ram semen, both in the extender and during the freezing and thawing process. In addition, the data suggest that the antioxidants Trolox and catalase may be used to control the oxidative stress imposed on ram spermatozoa by the cryopreservation process. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ram semen; Freezing; Catalase; Trolox-C; Lipid peroxidation; Hydrogen peroxide